Creating a birth cohort to examine RSV bronchiolitis hospital admission rates among term and preterm infants in England. (24th May 2012) - Murray, J; Bottle, A; Sharland, M; Modi, N; Aylin, P; Majeed, A; Saxena, S
Abstract : Aims: We aimed to examine Respiratory Syncytial Virus (RSV) bronchiolitis hospital admission rates among term and preterm infants in England. Methods: We developed a population-based birth cohort with follow-up to age 1 year using the Hospital Episode Statistics (HES) database. We identified individual birth records from a twelve month period (01/04/2007 to 31/03/2008), from 71 NHS hospitals across England (where >90% of their birth records contained complete recording of key variables, birth weight and gestational age) and linked to subsequent hospital admission records. Infants were considered preterm if, their birth weight was less than 1500 g, their gestational age at birth was less than 37 weeks or they had a diagnostic code indicating short gestation. We identified emergency admissions with a primary diagnosis of acute bronchiolitis and then calculated bronchiolitis hospital admission rates among term and preterm born infants. Results: Among our birth cohort (n=296618), there were 7189 admissions to hospital with bronchiolitis during the first year of life, 24.2 admissions per 1000 infants under 1 year (95% CI 23.7 to 24.8). In total 12% (880/7189) of infants admitted with bronchiolitis were born preterm. Admission rates were higher among infants born preterm (52.9 per 1000 infants (95% CI 49.5 to 56.5)) compared with those born at term (22.5 per 1000 infants (95% CI 22.0 to 23.1)). The modal age group for bronchiolitis admissions was infants aged 1 month. The median age of bronchiolitis admission among infants born preterm was 137 days (IQR = 75 to 227) compared with 118 days (IQR = 59 to 207) among infants born at term (p<0.001). The median length of bronchiolitis admission among preterm infants was 1 day (IQR = 0 to 4 days) and among infants born at term was also 1 day (IQR = 0 to 3 days). Conclusion: Our study shows that 88% of infants admitted to hospital with bronchiolitis in England are born at term and many are admitted for just 1 day. The peak in RSV bronchiolitis admissions at age 1 month is earlier than previously reported in other developed countries. These findings have important implications for both active and passive immunisation policies.